JARINGAN PROSES SOSIALISASI NILAI SENI UKIR DI KABUPATEN JEPARA - Slamet Subiyantoro (PAEDAGOGIA, 2009)
This research aims at describing (1) the agents participating in preserving carving art values, (2) the agents involved in the network of the direct socialization process of carving art values, and (3) the agents involved in the network of the indirect socialization process of carving art values. Descriptive-qualitative approach was applied in the research. The techniques of data collecting used were in-depth interview, participatory observation, and content analysis. The quotation technique was based on purposive and snowball samplings. To keep the data valid, triangulation and informant re-checking were carried out and interactive model was used as the analysis technique. From the result of the research, it can be concluded that the existence of carving art in Jepara was much influenced by the network of socialization process, both direct and indirect, of carving art values. The network of direct socialization process ran through formal and informal ways; while the network of indirect socialization process ran through informal ways. The formal socialization took place in educational institutions from Kindergartens, Elementary Schools, to Junior High Schools, while the informal socialization took places in apprenticeship and business environment. The indirect socializationtookplaceinfamilies,amongpeerfriends,inmosques,andinmassmedia.